(untitled) (JournalNX - A Multidisciplinary Peer Reviewed Journal, 2023)
Digital competencies play a key role in today’s world of education. Preparing future computer science teachers to use modern information technology and educate students is important for a successful career in the profession. However, in order to effectively integrate digital competencies into the educational process, it is necessary to monitor and evaluate these skills. In this chapter, we will consider methods for assessing digital competencies in future computer science teachers and the development of assessment criteria.